Завещание Мадонны - Жукова-Гладкова Мария Вадимовна (Двойной крутой детектив, 2015)
Экземпляры: ф.3 (20180515) / Инвентарный номер: 58292 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ж 86 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44